2015
DOI: 10.1080/15313220.2015.1026474
|View full text |Cite
|
Sign up to set email alerts
|

Digital or Printed Textbooks: Which do Students Prefer and Why?

Abstract: Despite the fact the many textbook publishers offer several of their titles in digital format, the sale of e-textbooks have been less than stellar. This study investigates factors in the adoption of e-textbooks. Specifically, it examines students' preferences toward printed versus electronic textbooks, and why they prefer one to the other. In general, students still prefer printed textbooks to electronic textbooks. The primary reason for their preference was because the students simply prefer print to digital.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
2
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 24 publications
2
60
2
6
Order By: Relevance
“…Most studies have shown that a majority of students prefer print to digital (e.g., Millar & Schrier, 2015;Woody, Daniel, & Baker, 2010). For example, data from 655 student respondents of the 2011 Electronic Book and eReader Device survey revealed that if the choice of textbook for a course were entirely theirs, 75% of students would opt for a print textbook over a digital one (NACS OnCampus Research, 2011).…”
Section: Print Vs Digital Textbooksmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies have shown that a majority of students prefer print to digital (e.g., Millar & Schrier, 2015;Woody, Daniel, & Baker, 2010). For example, data from 655 student respondents of the 2011 Electronic Book and eReader Device survey revealed that if the choice of textbook for a course were entirely theirs, 75% of students would opt for a print textbook over a digital one (NACS OnCampus Research, 2011).…”
Section: Print Vs Digital Textbooksmentioning
confidence: 99%
“…Recent research that explored the reasons for this general preference has found contradictory results. For example, an inability to take notes or highlight text and greater convenience were among the top-cited reasons for a preference for print (Millar & Schrier, 2015). On the other hand, aside from lower cost, greater convenience (e.g., ability to access e-textbooks anywhere, access e-textbooks offline, and store many e-textbooks on the same device) is typically the largest factor that drives e-textbook adoption 3 (de Noyelles et al, 2015).…”
Section: Print Vs Digital Textbooksmentioning
confidence: 99%
“…Bu noktada ise dijital platformların daha da geliştirilmesi ve iyileştirilmesi gerekliliği ortaya çıkmaktadır (Myrberg ve Wiberg, 2015). Çünkü, öğrencilerin büyük bir kısmı elektronik kitap okumak için daha gelişmiş e-reader türü cihazlar yerine laptop bilgisayarlarını kullanmaktadırlar (Millar ve Schrier, 2015).…”
Section: Literatür Incelemesiunclassified
“…Millar ve Schrier (2015)'in araştırmasına katılan 190 üniversite öğrencisinin büyük bir kısmı (%57,4) kağıt kitapları tercih ederken, daha az bir kısmı (%25) ise elektronik ders kitaplarını tercih etmiştir. Elektronik ders kitabını tercih edenlerin en önemli iki gerekçesi; (1) bütün kitapların bir arada olması ve (2) basılı kitaba göre daha fazla kolaylık sağlamasıdır.…”
Section: Neden Dijital Ortam?unclassified
See 1 more Smart Citation